2021
DOI: 10.3390/plants10112492
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and Antioxidant Effects of Guishe Extract from Agave lechuguilla, a Mexican Plant with Biotechnological Potential, on Streptozotocin-Induced Diabetic Male Rats

Abstract: In the present study, we used a by-product from Agave lechuguilla (guishe) to test its antidiabetic effect, hypolipidemic activity, and capacity to mitigate the oxidative stress in kidney mitochondria from streptozotocin-induced diabetic rats. Orally, a crude aqueous extract from lyophilized guishe was administered over 5 weeks at different doses. Blood glucose and body weight were monitored. Also, blood chemistry, bilirubin, and alanine aminotransferase were assayed. Furthermore, the activity of catalase, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…These findings are consistent with prior research that found flavonoids to have hepatorenal protective properties [ 29 ]. Rosinidin molecules significantly suppress amylase enzymes, signifying anti-diabetic effects; this is consistent with prior studies on other flavonoids [ 30 , 31 , 32 ]. Furthermore, rosinidin protects vital tissues including the pancreas, thereby lowering risks of diabetes-related complications.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with prior research that found flavonoids to have hepatorenal protective properties [ 29 ]. Rosinidin molecules significantly suppress amylase enzymes, signifying anti-diabetic effects; this is consistent with prior studies on other flavonoids [ 30 , 31 , 32 ]. Furthermore, rosinidin protects vital tissues including the pancreas, thereby lowering risks of diabetes-related complications.…”
Section: Discussionsupporting
confidence: 91%
“…The results revealed that 20 mg/kg BW of the purified extract significantly reduced oxidative damages in both the kidneys and the liver, and such effect has been related to the high antioxidant capacity of the characterized phytochemicals [ 60 ]. In addition to polyphenols, antioxidative effects, and mitigation of serum lipid abnormalities observed in diabetic Wistar rats treated with Agave lechuguilla by-product extracts were attributed to the saponins (triterpenoid glycosides), and the effective concentration was established at 300 mg/kg BW [ 83 ].…”
Section: The Role Of Plants In Renal Pathophysiologymentioning
confidence: 99%